The effects of lecturer's model e-comments on graduate students' peer e-comments and writing revision. Issue 3 (12th May 2021) - Pham, V. P. Ho
Abstract: Earlier research efforts have succeeded in training students to enhance their skills commenting on peer writing and using peer and lecturer comments to revise their writing, but few studies have investigated (1) the effect of the lecturer's e-comments on the quality of peer e-comments, and (2) the relative effectiveness of lecturer and peer e-comments on the revisions made by student writers. The current study begins to fill these gaps in the literature. Fifty graduate students enrolled in the course called Academic Writing participated in the study. The study collected and analyzed quantitative data from student writer drafts and revisions, the lecturer's model e-comments, and peer e-comments. The study found that qualified e-comments (revision-oriented comments) addressing global issues as opposed to local issues in student writing were different in statistically significant ways during the peer comment activities of the course. The effects of lecturer e-comments and peer e-comments on student writer revisions, however, showed no statistically significant differences. The study indicates that the lecturer's model e-comments had great effect in improving the peer commenting skills and writing quality of the graduate student writers. The effect of two incidentals, contributing factors, increased exposure time and reduced instructor load, are briefly discussed.